Diversity of Crops and Cropping Systems in Jessore Region - Dewan, MMR; Rashid, M Harun Ar; Nasim, M; Shahidullah, SM (Bangladesh Rice Journal, 2018)
Thorough understanding and a reliable database on existing cropping patterns, cropping intensity and crop diversity of a particular area are needed for guiding policy makers, researchers, extensionists and development workers for the planning of future research and development. During 2016 a study was accomplished over all 34 upazilas of Jessore region using pre-tested semi-structured questionnaire with a view to document the existing cropping patterns, cropping intensity and crop diversity in the region. The most dominant cropping pattern Boro−Fallow−T. Aman occupied 32.28% of net cropped area (NCA) of the region with its distribution in all upazilas. The second largest area, 5.29% of NCA, was covered by single Boro, which was spread over 24 upazilas. A total of 176 cropping patterns were identified in the whole region under the current investigation. The highest number of cropping patterns was identified 58 in Kushtia sadar upazila and the lowest was 11 in Damurhuda upazila of Chuadanga district. The lowest crop diversity index (CDI) was reported 0.852 in Narail sadar upazila followed by 0.863 in Jessore sadar upazila. The highest value of CDI was observed 0.981 in Daulatpur followed by 0.978 in Bheramara upazila of Kushtia district. The range of cropping intensity values was recorded 175−286%. The maximum value was for Sreepur of Magura district and minimum for Abhaynagar of Jessore district. As a whole the CDI of Jessore region was calculated 0.955 and the average cropping intensity at regional level was 229%. Bangladesh Rice j. 2017, 21(2): 185-202